2021
DOI: 10.1002/jcp.30620
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR‐185‐5p as modulator of periostin synthesis and smooth muscle contraction in asthma

Abstract: Asthma is a chronic respiratory disease produced by an aberrant immune response that originates with breathing difficulties and cough, through airway remodeling. The above pathophysiological events of asthma emerge the regulators of effectors, like epigenetics, which include microRNAs (miRNAs) who perform post-transcriptional regulation, controlling diverse pathways in respiratory diseases. The objective of the study was to determine how miR-185-5p regulates the secretion of periostin by airway structural cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A potential reason would be that, as discussed above, miR-185-5p could contribute to aggravated inflammation, Th1/ Th2 imbalance, lung damage, etc., hence, exacerbating childhood asthma. 14,15,19,30 As a result, miR-185-5p was correlated to exacerbation risk in childhood asthma patients. Notably, miR-185-5p regulates periostin synthesis and smooth muscle contraction to participate in the pathology of asthma.…”
Section: Childhood Asthmamentioning
confidence: 99%
See 3 more Smart Citations
“…A potential reason would be that, as discussed above, miR-185-5p could contribute to aggravated inflammation, Th1/ Th2 imbalance, lung damage, etc., hence, exacerbating childhood asthma. 14,15,19,30 As a result, miR-185-5p was correlated to exacerbation risk in childhood asthma patients. Notably, miR-185-5p regulates periostin synthesis and smooth muscle contraction to participate in the pathology of asthma.…”
Section: Childhood Asthmamentioning
confidence: 99%
“…The potential reasons would be as follows: (1) miR-185-5p could trigger the imbalance of Th1/Th2 cells and aggravate the inflammation, leading to the onset of childhood asthma 14,15 and (2) miR-185-5p could also modulate the perisynthesis and smooth muscle contraction to induce childhood asthma, 19 thus, miR-185-5p could reflect higher childhood asthma susceptibility.…”
Section: Childhood Asthmamentioning
confidence: 99%
See 2 more Smart Citations
“…Other research described a novel regulatory pathway involving miR-19a, which is critical to the severe asthma phenotype, in which down-regulation of miR-19a expression could be explored as a potential new therapy to modulate epithelial repair in asthma by targeting the TGFβR2 gene [ 51 ]. We recently reported that miR-185-5p, a miRNA previously associated with asthma disease in serum, was able to control the synthesis of the matricellular protein periostin in airway structural cells, and could modulate the contraction of bronchial smooth muscle cells through the regulation of RhoA and CDC42, thereby making it a promising therapeutic target [ 52 ].…”
Section: Mirna Regulation Of Asthma Pathogenesismentioning
confidence: 99%